Unlocking Social Media Success: How Prosumers Drive Brand Engagement through Authentic Conversations with Consumers - Malodia, Suresh; Filieri, Raffaele; Otterbring, Tobias; Dhir, Amandeep (British journal of management, 2024)
This research examines whether prosumer‐generated (vs. firm‐generated) content fosters consumer engagement through content relevance and perceived content sponsorship. Four between‐subjects experiments (N = 1048) show that prosumer‐led (vs. firm‐led) conversations, mediated by perceived content sponsorship and content relevance, generate higher engagement. Furthermore, consumer engagement increases significantly when prosumers share hedonic content and disclose information about their identity. A fifth study, a qualitative investigation with brand managers and marketing practitioners, further validates and extends these findings, providing nuanced insights in the form of four prosumer‐led engagement strategies for consumer engagement. These strategies have practical implications for companies seeking to leverage prosumers in social media marketing. Together, the current work broadens the research scope of prosumers from content co‐creators to drivers of brand engagement, while revealing the factors that increase the effectiveness of prosumer‐led social media content. Specifically, this research suggests that content type and authenticity are fundamental criteria for choosing a prosumer to engage social media brand followers. From a managerial viewpoint, the findings indicate that companies should identify, connect, and engage with online prosumers, as they will actively contribute towards improving consumer engagement levels.